Web Application Development for Scientific Data - Nathaniel Bennett; Rebekah David; Emily Watson (UNC Test Journal, 2013)
Scientific data is often not very useful in its raw formats, especially in discovery-based science, where hypotheses are formed by analyzing large multivariate datasets. Scientists who work on experimental data need to formulate context around the datasets they are analyzing. Web application frameworks are tools for creating context, visualizing and facilitating collaboration needed to understand many different types of commercial and analytical information. This research will entail finding a suitable web application framework, then designing and developing a system for Dr. Airat Khasanov, a chemistry research scientist at UNC Asheville. This research lends itself well to future students as well as the broader scientific community. It also offers insight into how conventional, open and easily accessible web tools can be used to assist data-driven science in forming hypotheses. Furthermore, it may serve as a template for further interdisciplinary collaboration.